Increasing Block Rate Electricity Pricing and Propensity to Purchase Electric Appliances: Evidence from a Natural Experiment - Salim Turdaliev (Charles University in Prague, Institute of Economic Studies (IES), 2021)
This paper provides empirical evidence on the relationship between increasing-block-rate (IBR) pricing of electricity and the propensity of households to buy major electric appliances. I use variation from a natural experiment in Russia that introduced IBR pricing for residential electricity in a number of experimental regions in 2013. The study employs household-level panel data which records, among others, whether the household has purchased any major electric appliances during the last 3 months. Using difference-in-differences specification I show that in the regions with IBR pricing the purchase of major electric appliances has increased by more than 25 percent (2 percentage points). The findings suggest that price-based energy policies may be an effective tool in shaping the behavior of households.
Keywords: Q3; Q4; D1; D9; 330; appliances; increasing-block-rate tariff; electricity prices; energy efficiency gap